(untitled) (Voice of Teacher, 2023)
The modern globalized capitalistic economic system blended with never ending hunger of accumulation of wealth has intensified the process of industrialization, urbanization, over use of natural resources, deforestation, anti-metabolic processes creating imbalance in the carbon cycle, bringing changes in the global climate and forming problems in the environment. Such consequences brought changes in the adaptation behavior of the people of Kathmandu Valley. This study aims to focus on the perception and adjustment practices of kathmandu valley people with regard to change in climate and environment. In this study, four elderly people of different areas of Kathmandu valley have been selected purposively for acquiring information about the perception on climate change and environment of Kathmandu valley and change in the practices of people for coping with the changing context. Information has been collected through several hours of informal interview with the sampled people within the period of one month. There is adverse impact of capitalistic economic system and associated socio-cultural practices on the environment of Kathmandu valley causing change in the climatic condition and enforcing local people to change in their practices and behavior for better adjustment.